2001
DOI: 10.1051/0004-6361:20011054
|View full text |Cite
|
Sign up to set email alerts
|

Probable asteroidal origin of the Tunguska Cosmic Body

Abstract: Abstract. The complete characterisation of the Tunguska event of 30th June 1908 is still a challenge for astrophysicists. We studied the huge amount of scientific literature to select data directly available from measurements and we introduced parameters calculated by the application of models, and evaluated other possibilities. We then selected a range of meaningful atmospheric trajectories, from which we extracted a set of possible orbits. We obtained 886 orbits, which were used to estimate the probabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 38 publications
2
39
0
Order By: Relevance
“…The present results do not contradict this conclusion. At the same time, the results of recent theoretical calculations give evidence in favor of both the comet (Bronshten, 2000) and asteroid (Farinella et al, 2001) hypotheses. This distinction has lost its sharpness after the recent discovery of asteroids that behave like comets and comets that behave like asteroids and the double designation of some of these objects (Yeomans, 2000).…”
Section: Carbonmentioning
confidence: 94%
“…The present results do not contradict this conclusion. At the same time, the results of recent theoretical calculations give evidence in favor of both the comet (Bronshten, 2000) and asteroid (Farinella et al, 2001) hypotheses. This distinction has lost its sharpness after the recent discovery of asteroids that behave like comets and comets that behave like asteroids and the double designation of some of these objects (Yeomans, 2000).…”
Section: Carbonmentioning
confidence: 94%
“…Due to the remote location of the impact site only two people and several reindeer herds were reported killed in this event. Evidence for the cosmic origin of the impactor is given by the extraterrestrial particles which had been found in the burned trees (Farinella et al 2001). …”
Section: Examples Of Impactsmentioning
confidence: 99%
“…Two additional and more complete analyses were independently performed by Ben-Menahem (1975) and Pasechnik (1976). They found practically the same value for the time the seismic and aerial waves started (see Table 18.1, updated from Farinella et al 2001). Pasechnik (1976) calculated that the time of the explosion in the atmosphere was 7-30 seconds earlier depending on the height and energy of the explosion; this interval was subsequently reduced to 2-20 seconds (Pasechnik 1986).…”
Section: Explosion Timementioning
confidence: 86%
“…This field research has been strengthened by theoretical studies and modeling. In a recent paper (Farinella et al 2001), a sample of possible TCB orbits has been constructed and a dynamic model was used to compute the most probable source of a TCB placed on each of these orbits. The results of calculations gave a greater probability for a TCB coming from an asteroidal source (83%), than from a cometary source (17%).…”
Section: Comet or Asteroid?mentioning
confidence: 99%
See 1 more Smart Citation